African Buffalo Optimization Algorithm for PID parameters tuning of Automatic Voltage Regulators - Odili, Julius Beneoluchi; M. N. M., Kahar; Noraziah, Ahmad (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
To obtain stability of electric power generating system, there is the need for an Automatic Voltage Regulator (AVR) component. The effectiveness of the AVR is traceable to the proper tuning of the Proportional, Integral and Derivative (PID) parameters within the AVR. Our innovation is the successful use of the African Buffalo Optimization Algorithm to tune PID parameters for optimum efficiency and effectiveness.